(untitled) (Acta Polytechnica CTU Proceedings, 2021)
High-speed rail lines should make it possible to fully replace air transport over the medium distances of Europe (about 500 km). In the Czech Republic, they are beginning to design. Estimates suggest that in five years, the first sections could begin to physically originate and within ten years, they will begin to ride on them. Is it possible that the scenario and the continuous extension of deadlines accompanying the completion of the backbone network will be repeated? This article discusses the options from the project management perspective and the idea of construction 4.0 to prevent this.